49 Supra gastric belching symptoms, prevalence and associated disease. (5th April 2017) - Elsafi, G; Alhanaee, A; Barry, L; Quinlivan, L; Farman, M; McCarthy, J; Buckley, M
Abstract : Background: Supragastric belching (SGB) is considered a behavioural disorder where air is ingested in to eosophagus and immediately expelled again; it can result in symptoms of excessive belching and has a significant impact on quality of life. With the advent of the intraluminal impedance recording technique, it has become possible to monitor the passage of air through the oesophagus, either in ab-oral or ad-oral directions. Aim: Determine the prevalence of excessive SGB within our tertiary referral gastrointestinal physiology unit and evaluate the predominant presenting symptoms and examine its association with gastro-esophageal reflux disease and motility disorders. Method: Data was collected retrospectively from our data base system, we reviewed 442 reports of 24 hours PH-Impedance and high resolution oesophageal manometry from January 2015 to December 2016. Symptoms were reviewed from patients' charts. These included the predominant presenting symptom, symptoms of acid reflux and heartburn, regurgitation and dysphagia. Results: A total of 98 (22%) patients were found to have excessive SGB. predominant presenting symptom was heartburn (55%), only 18% had pathological acid exposure. Dysphagia was reported in 23% and regurgitation in 7%. only 7% presented with isolated symptom of belching, Esophageal hypomotility was seen in 48%. Conclusions: Excessive SGB was common finding in 24 hours PH-impedance manometry studies, the main predominant symptom was heartburn, and there appears to be an association with oesophageal hypomotility and to a lesser extent with gastroeosphageal reflux disease.